Characterization and shelf life testing of bigscale goatfish (Pseudopenaeus grandisquamis) tocino produced in Cadiz City, Negros Occidental - Lao-as, Kristen Anne Villa
Unpacked and packed bigscale goatfish tocino produced in Cadiz City, negros Occidental was characterized in terms of its physico-chemical properties (MC, aw, pH, TSS, salt content, TVB-N and TMA contents).